2010
DOI: 10.1159/000275501
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Aneurysmal Subarachnoid Hemorrhage in an Indian Population

Abstract: Background: Aneurysmal subarachnoid hemorrhage (aSAH) has a mortality rate as high as 50%. The prevalence of intracranial aneurysms from various parts of India varies from 0.75 to 10.3%, with higher numbers of cases being diagnosed due to the increasing age of the population and improvements in imaging techniques. However, little is known about the attributable risk factors of aSAH in the Indian population. Methods: Using a case-control study we estimated the risk of factors such as hypertension, cigarette smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 32 publications
2
24
2
Order By: Relevance
“…Instead, the association between type 2 diabetes and sIA disease has remained unclear. Unlike our study and the cohort of 329 cases of SAH from sIA published in 1984 (37), three recent studies (2022) and our present review of the literature from the six published ones suggested that diabetes is a protective factor for SAH (Table 1; Fig. 1).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Instead, the association between type 2 diabetes and sIA disease has remained unclear. Unlike our study and the cohort of 329 cases of SAH from sIA published in 1984 (37), three recent studies (2022) and our present review of the literature from the six published ones suggested that diabetes is a protective factor for SAH (Table 1; Fig. 1).…”
Section: Discussioncontrasting
confidence: 78%
“…Instead, the association between type 2 diabetes and sIA disease has remained unclear. Three recent studies (2022) and our present review of the literature suggest that diabetes is a protecting factor for rupture of sIA (Table 1; Fig. 1 A ) (2329).…”
mentioning
confidence: 51%
“…The extremely low incidence rate invalidates a routine screen. However, in taking care of patients with lupus, one should aggressively control lupus activity and other well‐established risk factors of SAH, including hypertension, bleeding tendency, and cigarette smoking (22). Furthermore, in SLE patients with severe headache, despite a relatively young age, SAH should be suspected as an important differential diagnosis, especially in those with higher lupus activity or a history of recurrent platelet or red blood cell transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking causes direct injury to endothelial cells [16], oxidation of low-density lipoprotein[17], and acceleration of thrombus formation through increased plasma fibrinogen [18], increased platelet aggregability [19] and decreased fibrinolytic activity [20], all of which are associated with the development of atherosclerotic diseases such as ischemic stroke and CHD. Smoking is also considered to cause the formation, growth and rupture of intracranial aneurysms [21,22], probably due to an elastase/α 2 -antitrypsin imbalance in the artery wall [23], leading to an elevated risk of subarachnoid hemorrhage [21,22,24]. …”
Section: Discussionmentioning
confidence: 99%